(untitled) (Journal of the College of Education for Women, 2019)
The symbolic image refers to the thing which symbolizes it and embodiesthe meaning in the recipient’s conscience taking into consideration thegeneral context. The thesis of Al-Nibahi is based on a simple tale stating thatthe palm, which had a venerable status among the Arabs because of its goodorigin, ingrained springing and its delicious fruit, lost its status; however, itcontinued standing in veneration and silence near the wall of Alhambra. Thispalm has complained from harm and negligence, as it has warned of thewaste, and awakened the people to present the defect of its harm. Thisresearch finds through these ideas that the palm was a symbol of the remains of the Arabic sovereignty which restricted to Granada. The complaints of thepalm warned and referred to the next threat. The presence of this image hasachieved by several rhetorical arts, the techniques of objective narration byenlistment, description and presentation, and the techniques of subjectivenarration by dialogue and retrieval. The symbol transforms the naturalphenomena into an idea, and an idea into an image; thus, the symbol has asubjective meaning at the time it refers to unlimited meaning out of it anddepending on it.